Peningkatan Mutu Pembelajaran Sintaksis melalui Lesson Study for Learning Community (LSLC) - Raden Mekar Ismayani; Latifah Latifah; Yusep Ahmadi (Indonesian Language Education and Literature, 2019)
There are still many Indonesian language teacher candidates who have not mastered syntax. This article describes the results of Lesson Study for Learning Community (LSLC) activities carried out in the Indonesian language education study program STKIP Siliwangi (now IKIP Siliwangi) with the aim of regular students, fifth semester who are taking a syntax course. The learning method used is discovery learning plus because in its implementation it integrates the use of mind mapping methods in the learning steps of discovery learning methods. From the results of data analysis shows that the application of discovery learning methods plus through LSLC can improve student learning outcomes in syntactic courses. Improved learning outcomes can be seen from the recap percentage, in the first cycle students who were able to answer questions were 52.19%, cycle 2 59.06%, and cycle 3 were 86.56%. In addition, the four abilities of students who were the focus of this program's observations also increased.Masih banyak calon guru bahasa Indonesia yang belum menguasai sintaksis. Artikel ini mendeskripsikan hasil kegiatan Lesson Study for Learning Community (LSLC) yang dilaksanakan pada program studi pendidikan bahasa Indonesia STKIP Siliwangi (sekarang IKIP Siliwangi) dengan sasaran mahasiswa reguler, semester lima yang sedang menempuh mata kuliah sintaksis. Metode pembelajaran yang digunakan adalah discovery learning plus karena dalam pengimplementasiannya mengintegrasikan penggunaan metode mind mapping dalam langkah-langkah pembelajaran metode discovery learning. Dari hasil analisis data menunjukkan bahwa penerapan metode discovery learning plus melalui LSLC dapat meningkatkan hasil belajar mahasiswa dalam mata kuliah sintaksis. Peningkatan hasil belajar dapat dilihat dari rekap persentase, pada siklus 1 mahasiswa yang mampu menjawab soal sebesar 52,19%, siklus 2 59,06%, dan siklus 3 sebesar 86,56%. Selain itu, empat kemampuan mahasiswa yang menjadi fokus pengamatan program ini, juga mengalami peningkatan.